2010
DOI: 10.1152/ajpcell.00072.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate signaling is involved in skeletal muscle regeneration

Abstract: ) is a bioactive lipid known to control cell growth that was recently shown to act as a trophic factor for skeletal muscle, reducing the progress of denervation atrophy. The aim of this work was to investigate whether S1P is involved in skeletal muscle fiber recovery (regeneration) after myotoxic injury induced by bupivacaine. The postnatal ability of skeletal muscle to grow and regenerate is dependent on resident stem cells called satellite cells. Immunofluorescence analysis demonstrated that S1P-specific rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 48 publications
2
72
0
Order By: Relevance
“…This action of S1P on satellite cell activation and muscle regeneration is in line with the proliferative, proinflammatory (through COX-2) and antiapoptotic (through inhibition of caspase-3 and BAX) functions of S1P-mediated pathways in general. Accumulating evidence indicates that S1P, being one of the more soluble sphingolipids, acts through S1P receptors (S1PRs; a group of highaffinity G protein-coupled receptors) on satellite cells in an autocrine/paracrine fashion (76,122). In addition, abnormal modulation of S1P activity is also involved in the pathology of muscular dystrophy (as exemplified in mdx mice) (317).…”
Section: /Sca1mentioning
confidence: 99%
“…This action of S1P on satellite cell activation and muscle regeneration is in line with the proliferative, proinflammatory (through COX-2) and antiapoptotic (through inhibition of caspase-3 and BAX) functions of S1P-mediated pathways in general. Accumulating evidence indicates that S1P, being one of the more soluble sphingolipids, acts through S1P receptors (S1PRs; a group of highaffinity G protein-coupled receptors) on satellite cells in an autocrine/paracrine fashion (76,122). In addition, abnormal modulation of S1P activity is also involved in the pathology of muscular dystrophy (as exemplified in mdx mice) (317).…”
Section: /Sca1mentioning
confidence: 99%
“…The expression of several transcription factors, including STAT3, was shown to be upregulated in diaphragm muscles from 6 week old mdx mice compared to WT mice [57]. Sphingosine-1 phosphate (S1P) is a bioactive lipid that modulates the activity of many different pathways (e.g., AKT signaling and Ras/MAP kinase cascade), and has been implicated in the activation of satellite cells [24,94,95]. In a study evaluating the role of S1P in muscle satellite cell function, results demonstrated that S1P catabolism was associated with lower STAT3 activation and poor satellite cell function [96].…”
Section: Stat3 Activation In Muscular Dystrophiesmentioning
confidence: 99%
“…Two sphingosine-1-phosphate receptors, S1P 1 and S1P 3 , are expressed by quiescent satellite cells and are localized to the sarcolemma and T-tubules of skeletal muscle fibers; S1P 1 is found at the neuromuscular junction (125). Regeneration of soleus muscle after injury stimulates the expression of these receptors, whereas administration of sphingosine-1-phosphate at the time of injury increases the cross-sectional area of regenerating fibers; conversely, administration of anti-sphingosine-1-phosphate antibody has the opposite effect, attenuating fiber growth (27). Sarcolemmal receptors are likely to mediate these trophic effects, suggesting that sphingosine-1-phosphate can function as a growth factor for muscle fibers.…”
Section: Sphingosine-1-phosphate and Its Receptormentioning
confidence: 99%
“…5). Danieli-Betto et al (27) demonstrated the capacity of sphingosine-1-phosphate to oppose fatigue. In vitro exposure of murine EDL to sphingosine-1-phosphate slowed the decline in force during fatiguing contractions; final force was 40% greater than control.…”
Section: Sphingolipids and Fatiguementioning
confidence: 99%